Planning green infraestructures as a mean to improve urban quality of life – lessons from the Bragança (Portugal) green plann - Gonçalves, Artur (2011)
Green spaces are regarded as essential elements in urban sustainability, performing diverse social, environmental and economical functions. Moreover, they are key elements in urban structure, as they can help balancing interactions between the landscape and urban artificial element. Braganca’s Green Plan is an innovative initiative consisting on a multidisciplinary and integrated approach to urban greening. Its methodology covered the following stages: firstly, a multidisciplinary study addressed local inner and outer city characteristics; secondly, a local green structure was defined including three central elements: an essential structure, a secondary structure and a network of green corridors, this proposal also relates to a Local Green Spaces Strategy; finally, a best practice guide was developed, oriented to the local reality, in order to support both institutions and inhabitants in their daily management of green spaces. As a result, a set of tools for land use planning and management are defined helping to promote a greener and sustainable future.